Personal and academic multicultural experiences, perceived multicultural counselling competence and multicultural counselling self-efficacy among Malaysian counsellor trainees - Harun, Maizatul Mardiana; Wan Jaafar, Wan Marzuki; Ismail, Asmah; Arifin, Suhaili (Universiti Putra Malaysia, 2024)
The counsellor trainees’ self-efficacy is indirectly influenced by what they have experienced in their personal or academic lives, and the experience does contribute to their knowledge, beliefs, and attitudes. Nevertheless, sufficient evidence to elaborate on the reciprocal interactions in the context of counselling is still limited. Therefore, this descriptive-correlational study intends to investigate the connection between Malaysian counsellor trainees’ perceived multicultural counselling competence and self-efficacy and their personal and academic multicultural experiences. All four instruments had been adapted and translated into Malay before being completed by 208 randomly selected counsellor trainees. According to the study’s findings, counsellor trainees scored high on academic multicultural experience but low on personal multicultural experience. They also gained high scores for multicultural counselling self-efficacy and moderate perceived multicultural counselling competence. Importantly, findings revealed substantial correlations between perceived multicultural counselling competence and self-efficacy with academic multicultural experience. Overall, the finding highlights the practice of experiential pedagogy in the multicultural counselling course and encourages collaborative efforts involving faculty members and programme providers in developing and sustaining students’ or counsellor trainees’ multicultural counselling competency and self-efficacy growth.